Endothelial dysfunction of vessels at lung cancer - Dumanskiy, Yu.V.; Stoliarova, O.Yu.; Syniachenko, O.V.; Iegudina, E.D. (Experimental Oncology, 2015)
Aim: To evaluate changes in indicators of endothelial function and their relationship with morphological forms of disease, stage of pathological process and tumor markers, by analysis the peripheral blood of lung cancer (LC) patients. Materials and Methods: 38 LC patients without metastases (mean age — 57 years) prior chemo- and radiotherapy were included in the study. The duration of the disease manifestation was 18 months. 21% of patients had small cell LC, and the rest — non-small cell LC. The ratio of patients with stages IA, IB, IIA, IIB, IIIA and IIIB LC was 1 : 3 : 3 : 4 : 4 : 4. The enzyme immunoassay, spectrophotometry, and statistical data analysis were used. Results: Endothelial dysfunction of vessels was characterized by increased blood levels of vascular endothelial growth factor (VEGF), endothelin-1 (ET1), homocysteine (HCys), cyclic guanosine monophosphate (cGMP), P-selectin (PSel) and nitrites (NO2) and simultaneously by decreased values of prostacyclin (PgI2). Those were observed in 100; 90; 76; 71; 50; 53 and 79% of LC cases, respectively. Disturbances of vascular endothelial function were associated with patient’s age, disease duration, and morphological form and LC stage. Such changes were observed in women with higher prevalence. The studied indices correlated with tumor markers, namely transforming growth factor beta (TGFβ1), fibronectin and osteopontin. Conclusion: Indices of vascular endothelial dysfunction in LC can be of diagnostic and prognostic value. Key Words: lung cancer, blood vessels, endothelium, endothelial dysfunction.